Child assistance training: Effects of training on parents’ knowledge in children’s language and numeracy development - Vidya Anindhita; Shally Novita; Puspita Adhi Kusuma Wijayanti; Lutfianya Assyifa Budi Santoso; Ajeng Nuranti Syafitri; Hellen La Batavee; Aurelia Felisha Jerome Tampubolon (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Preschool-age children show rapid development in various aspects of their development, including numeracy and language development. Various and appropriate stimulations are expected to optimize their development. Parents as the closest support system for preschool children have a very significant role, especially in helping children optimize their numeracy and language skills. Parents can play an optimal role if they understand children's numeracy and language development. In this community service program, parents are given training on "Optimizing the Learning Environment for Numeracy and Language in Preschool Children" which aims to increase parents' understanding of children's numeracy and language development and efforts to optimize it. The participants were 31 parents and Posyandu cadres in Jatimukti, Sumedang, West Java. Parents' understanding was measured through a pre-test questionnaire administered at the beginning of the training and a post-test questionnaire at the end of the training. The results showed a positive effect of the training on parents' understanding of children's numeracy and language development. Therefore, the results of this training recommend further trainings aimed at improving parents' understanding of language and numeracy development in preschool childrens.